Immune Landscape of CMV Infection in Cancer Patients: From “Canonical” Diseases Toward Virus-Elicited Oncomodulation - El Baba, Ranim; Herbein, Georges (Frontiers in Immunology, 2021)
Human Cytomegalovirus (HCMV) is an immensely pervasive herpesvirus, persistently infecting high percentages of the world population. Despite the apparent robust host immune responses, HCMV is capable of replicating, evading host defenses, and establishing latency throughout life by developing multiple immune-modulatory strategies. HCMV has coexisted with humans mounting various mechanisms to evade immune cells and effectively win the HCMV-immune system battle mainly through maintaining its viral genome, impairing HLA Class I and II molecule expression, evading from natural killer (NK) cell-mediated cytotoxicity, interfering with cellular signaling, inhibiting apoptosis, escaping complement attack, and stimulating immunosuppressive cytokines (immune tolerance). HCMV expresses several gene products that modulate the host immune response and promote modifications in non-coding RNA and regulatory proteins. These changes are linked to several complications, such as immunosenescence and malignant phenotypes leading to immunosuppressive tumor microenvironment (TME) and oncomodulation. Hence, tumor survival is promoted by affecting cellular proliferation and survival, invasion, immune evasion, immunosuppression, and giving rise to angiogenic factors. Viewing HCMV-induced evasion mechanisms will play a principal role in developing novel adapted therapeutic approaches against HCMV, especially since immunotherapy has revolutionized cancer therapeutic strategies. Since tumors acquire immune evasion strategies, anti-tumor immunity could be prominently triggered by multimodal strategies to induce, on one side, immunogenic tumor apoptosis and to actively oppose the immune suppressive microenvironment, on the other side.